The Effect of Green Purchase Attitudes, Subjective Norms, Perceived Behavioral Control, Environmental Concern on Product Purchasing Decisions - Nainggolan, Yunita; Harsoyo, Titik (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This research aims to determine the influence of green purchase attitudes, subjective norms, perceived behavioral control, environmental concerns on purchasing decisions for Kentucky Fried Chicken (KFC) products. This research uses a descriptive quantitative approach with correlation and regression analysis tools, to examine the level of relationship and influence that occurs between variables. The results of this research show that green purchase attitudes have no influence on purchasing decisions for Kentucky Fried Chicken (KFC) products with a significance value of 0.104 or above 0.05. The subjective norms variable has no influence on the decision to purchase Kentucky Fried Chicken (KFC) with a significance value of 0.881 or greater than 0.05. The variable perceived behavioral control has a positive and significant effect on the decision to purchase Kentucky Fried Chicken (KFC) with a significance value of 0.023 or less than 0.05 and the variable environmental concern has a positive and significant effect on the decision to purchase Kentucky Fried Chicken (KFC) products with a significance value of 0.008 or smaller than 0.05.